Косвенный метод вычисления объема яиц у колониально гнездящихся ржанкообразных птиц - Черничко, И.И.; Чичкин, В.Н. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 1999)
Материалом для данного сообщения послужили линейные и объемные промеры яиц в кладках 16 видов, преимущественно колониально гнездящихся ржанкообразных птиц, а также сопутствующих видов околоводных птиц. Проанализировано около 100 линейных и 700 объемных промеров яиц. Косвенный метод вычисления объема яиц необходим исследователю, когда в его распоряжении имеется только информация о линейных промерах, и нет другой возможности определить реальный объем яйца. Объем яиц затем определяется на основе общего коэффициента 0.509. Однако, исследования показали, что использование в расчетах общего для многих видов коэффициента приводит к искажению реальных величин на 10-18%. Наибольшие отклонения дают остроконечные формы яиц. Для нивелирования отклонений, при изучении экологии гнездования желательно применять видоспецифичные коэффициенты, которые определены нами для ряда фоновых видов. Использование коэффициента объема в качестве индекса формы позволяет использовать его в компьютерных базах данных, расчетах с использованием современных программ. Матеріалом для цього повідомлення послужили лінійні та об'ємні проміри яєць в кладках 16 видів, переважно колоніально-гніздуючих сивко подібних птахів, а також супутніх видів навколоводних птахів. Проаналізовано близько 100 лінійних і 700 об'ємних промірів яєць. Непрямий метод обчислення обсягу яєць необхідний досліднику, коли в його розпорядженні є тільки інформація з лінійних промірів, і немає іншої можливості визначити реальний обсяг яйця. Обсяг яєць потім визначається на основі загального коефіцієнта 0.509. Однак, дослідження показали, що використання в розрахунках загального для багатьох видів коефіцієнта призводить до спотворення реальних величин на 10-18%. Найбільші відхилення помічені у загостреної форми яєць. Для нівелювання відхилень, при вивченні екології гніздування бажано застосовувати видоспецифічі коефіцієнти, що визначені нами для декількох фонових видів. Використання коефіцієнта обсягу в якості індексу форми дозволяє використовувати його в комп'ютерних базах даних, розрахунках з використанням сучасних програм. Specific volume indices were determined based on direct measurements of linear dimensions (n ~ over 1000) and volume (n — over 700) of eggs. The data concern 16 species among which colonial Charadriidae predominate. Due to the time limit during a visit to a large colony it is often possible to take only linear measurements of eggs. Volume of eggs can be further determined using average index 0.509. To take into account species dependant and local variability of this coefficient we undertook a special analysis. For the majority of Charadriidae with pear-shaped eggs usage of the averaged index resulted in errors varying in the range of 10-18%. Overall error decreases if it is replaced by species specific indices. Such more precise indirect estimates of egg volume help to determine the incubation stage and hatching date in eggs with known mass. Options in application of volume index as a mathematical interpretation of egg shape are also discussed. Deviation of the egg volume which was measured directly from one calculated on the basis of species specific indices and linear dimensions can be expressed as variation in egg volume indices. According to our observations the index reflected even the smallest fluctuations in their shape and volume which were likely to be the function of feeding conditions, breeding terms, age of female, or position of nest and the colony.